Computer aided diagnostic tool for osteoporosis estimation. (25th September 2012) - Kumar, Shubhangi; Chatterji, S.; Thakur, Ritula; Kumar, Neelesh; Pankaj, Dinesh; Jindal, Rohit
Quantitative estimation of osteoporosis is the need of the hour. A majority of the older population worldwide is suffering from this disease. X-ray examinations are the most widely used method for osteoporosis estimation. It has severe limitation of examination being qualitative. The paper presents a novel approach by digitising the X-ray films using an X-ray digitiser and analysing the digitised films using LabVIEW Software. The method calculates the Osteoporosis Estimation Index on the basis of the ratio of histogram calculated for selected reference ROI and measurand ROI on the digitised patient images. The results indicate the accuracy and reliability of the technique over the present methods used.